Rancang Bangun Aplikasi Pembayaran Sumbangan Pembinaan Pendidikan (SPP) Pondok Pesantren Salafiyah Hidayatul Qomariyah Kota Bengkulu Menggunakan PHP Dan MySQL - Hasna Nabila; Indra Kanedi; Ricky Zulfiandry (Jurnal Media Infotama, 2025)
The development of information technology aims to facilitate the accurate access and management of information. Salafiyah Hidayatul Qomariyah Islamic Boarding School is one of the Islamic boarding schools that requires good financial administration services to manage student tuition payments because the current system still uses handwritten books (manual), which is ineffective and time-consuming. The programming language used is PHP with MySQL database, employing a qualitative method. This program will assist the treasurer of the Salafiyah Hidayatul Qomariyah Islamic Boarding School in managing or compiling reports on Educational Development Contributions (SPP) payments quickly and accurately. The results obtained indicate that the Educational Development Contribution (SPP) payment application functions well and can assist in the transaction and recording of Educational Development Contribution (SPP) payments at Salafiyah Hidayatul Qomariyah Islamic Boarding School as expected.